The use of innominate artery cannulation for antegrade cerebral perfusion in aortic dissection - Eden C. Payabyab; Jonathan M. Hemli; Allan Mattia; Alex Kremers; Sohrab K. Vatsia; S. Jacob Scheinerman; Efstathia A. Mihelis; Alan R. Hartman; Derek R. Brinster (Journal of Cardiothoracic Surgery, 2020)
Abstract Background Direct cannulation of the innominate artery for selective antegrade cerebral perfusion has been shown to be safe in elective proximal aortic reconstructions. We sought to evaluate the safety of this technique in acute aortic dissection. Methods A multi-institutional retrospective review was undertaken of patients who underwent proximal aortic reconstruction for Stanford type A dissection between 2006 and 2016. Those patients who had direct innominate artery cannulation for selective antegrade cerebral perfusion were selected for analysis. Results Seventy-five patients underwent innominate artery cannulation for ACP for Stanford Type A Dissections. Isolated replacement of the ascending aorta was performed in 36 patients (48.0%), concomitant aortic root replacement was required in 35 patients (46.7%), of whom 7 had a valve-sparing aortic root replacement, ascending aorta and arch replacement was required in 4 patients (5%). Other procedures included frozen elephant trunk (n = 11 (14.7%)), coronary artery bypass grafting (n = 20 (26.7%)), and peripheral arterial bypass (n = 4 (5.3%)). Mean hypothermic circulatory arrest time was 19 ± 13 min. Thirty-day mortality was 14.7% (n = 11). Perioperative stroke occurred in 7 patients (9.3%). Conclusions This study is the first comprehensive review of direct innominate artery cannulation through median sternotomy for selective antegrade cerebral perfusion in aortic dissection. Our experience suggests that this strategy is a safe and effective technique compared to other reported methods of cannulation and cerebral protection for delivering selective antegrade cerebral perfusion in these cases.